THEIR INTERESTS WERE CONNECTED: I. P. BORODIN AND N. I. VAVILOV - K. V. Manoylenko (Труды по прикладной ботанике, генетике и селекции)
The article is dedicated to two memorable dates - the l70th anniversary of the birth of I. P. Borodin, and the 130th anniversary of the birth of N. I. Vavilov.